Precocious Puberty in Boys with NR0B1 Variants - Atsushi Hattori; Maki Fukami (Endocrines)
Precocious puberty (PP) requires appropriate management to prevent short adult height, psychosocial issues, and other adverse outcomes. Genetic diagnosis potentially improves the management of PP. Pathogenic NR0B1 variants, which typically cause X-linked adrenal hypoplasia congenita, can also affect gonadal function. While boys with NR0B1 variants usually exhibit hypogonadotropic hypogonadism during adolescence, previous reports have suggested that minipuberty, a physiological transient activation of the hypothalamic–pituitary–gonadal axis during infancy, occurs in these patients and can persist beyond a typical duration. In rare cases, NR0B1 variants cause PP. PP associated with NR0B1 variants has unique features such as early onset and high serum testosterone levels that are often disproportionate to testicular size. Three underlying mechanisms have been proposed for the association between PP and NR0B1 variants: (1) adrenocorticotropic hormone (ACTH)-dependent, (2) gonadotropin-dependent, and (3) ACTH- and gonadotropin-independent mechanisms. The factors contributing to PP vary among cases. Determining the underlying mechanisms is crucial for adopting appropriate therapeutic strategies to control PP. However, as the detailed molecular networks mediating these mechanisms are largely unclear, further research is needed to pave the way for a more effective and personalized management of patients with PP associated with NR0B1 variants.